2017
DOI: 10.1101/104554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medicago truncatulacopper transporter 1 (MtCOPT1) delivers copper for symbiotic nitrogen fixation

Abstract: Summary• Copper is an essential nutrient for symbiotic nitrogen fixation. This element is delivered by the host plant to the nodule, where membrane copper transporter would introduce it into the cell to synthesize cupro-proteins.• COPT family members in model legume Medicago truncatula were identified and their expression determined. Yeast complementation assays, confocal microscopy, and phenotypical characterization of a Tnt1 insertional mutant line were carried out in the nodule-specific M.truncatula COPT fa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 82 publications
1
8
0
8
Order By: Relevance
“…Due to the advances in genomics methods and significant investment in legume research, the processes of nodule development and symbiotic nitrogen fixation are being unveiled at the molecular genetic level since the last decade (Qin et al, 2012;Collier and Tegeder, 2012;Tejada-Jiménez et al, 2017;Kryvoruchko et al, 2018;Wang et al, 2017a;Wang et al, 2017b;Yang et al, 2017). Nodulation starts with a chemical communication between Medicago truncatula roots and the free-living soil rhizobia.…”
Section: The Process Of Nodulation and Symbiotic Nitrogen Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the advances in genomics methods and significant investment in legume research, the processes of nodule development and symbiotic nitrogen fixation are being unveiled at the molecular genetic level since the last decade (Qin et al, 2012;Collier and Tegeder, 2012;Tejada-Jiménez et al, 2017;Kryvoruchko et al, 2018;Wang et al, 2017a;Wang et al, 2017b;Yang et al, 2017). Nodulation starts with a chemical communication between Medicago truncatula roots and the free-living soil rhizobia.…”
Section: The Process Of Nodulation and Symbiotic Nitrogen Fixationmentioning
confidence: 99%
“…Recently, Senovilla et al (2018) found MtCOPT1 to localize to the plasma membrane of cells in the differentiation, interzone and early fixation zones and hypothesized MtCOPT1 imports Cu 2+ from the apoplast to the cytosol to feed the metabolic processes of symbiotic nitrogen fixation. Their results confirm our findings and precluded the continuation of this work due to the lack of novelty for publication in a peer-reviewed journal.…”
Section: Notementioning
confidence: 99%
“…las plantas mot1.3-1 el contenido en molibdeno de los nódulos mutantes era significativamente mayor que el de los nódulos de plantas silvestres. Este tipo de acumulación de metal ya había Discusión 97 sido reportado previamente por Senovilla et al (2017) y Abreu et al (2017) para otros metales también necesarios para la FSN como el cobre y el zinc (Ibrikci & T. Moraghan, 1993;Seliga, 1993). En dichos trabajo se muestra que plantas de M. truncatula que no expresan el transportador de cobre MtCOPT1, o el transportador de zinc MtZIP6, ambos localizados en la membrana plasmática de las células infectadas de los nódulos, presentan acumulación de cobre o zinc, respectivamente, en los nódulos.…”
Section: La Mutación Deunclassified
“…thaliana que están localizados en el parénquima xilemático, y su mutación causa clorosis intervenal, debido a que complejos hierro-NA no son capaces de salir del xilema hacia el mesófilo de la hoja (Waters et al, 2006 (Senovilla et al, 2017, Tejada-Jiménez et al, 2017. MtCOPT1 es específico de nódulo y se localiza en la membrana plasmática de las células de la zona de infección, donde es capaz de introducir Cu + .…”
unclassified
“…MtCOPT1 es específico de nódulo y se localiza en la membrana plasmática de las células de la zona de infección, donde es capaz de introducir Cu + . En mutantes copt1-1, la disminución en la entrada de Cu + hacia los bacteroides, provoca una disminución de actividad nitrogenasa respecto a las plantas de tipo silvestre, que es debida a un descenso en la actividad citocromo oxidasa tipo-cbb3 de la bacteria (Senovilla et al, 2017 Sin embargo, previo a esta tesis doctoral no existe un candidato claro para mediar la entrada de hierro en las células infectadas con rizobios. A priori, MtZIP6 podría realizar esta función, dado que cuando se expresa en levadura es capaz de complementar fenotipos basados en defectos en la entrada de hierro en la célula (López-Millán et al, 2004).…”
unclassified